Manganese toxicity in the central nervous system: the glutamine/glutamate‐γ‐aminobutyric acid cycle. (22nd April 2013) - Sidoryk‐Wegrzynowicz, M.; Aschner, M.
Abstract Manganese (Mn) is an essential trace element that is required for maintaining proper function and regulation of numerous biochemical and cellular reactions. Despite its essentiality, at excessive levels Mn is toxic to the central nervous system (CNS). Increased accumulation of Mn in specific brain regions, such as the substantia nigra, globus pallidus and striatum, triggers neurotoxicity resulting in a neurological brain disorder, termed manganism. Mn has been also implicated in the pathophysiology of several other neurodegenerative diseases. Its toxicity is associated with disruption of the glutamine (Gln)/glutamate (Glu)‐γ‐aminobutyric acid (GABA) cycle (GGC) between astrocytes and neurons, thus leading to changes in Glu‐ergic and/or GABAergic transmission and Gln metabolism. Here we discuss the common mechanisms underlying Mn‐induced neurotoxicity and their relationship to CNS pathology and GGC impairment.